2013
DOI: 10.1123/japa.21.1.71
|View full text |Cite
|
Sign up to set email alerts
|

Increased Muscle Size and Strength From Slow-Movement, Low-Intensity Resistance Exercise and Tonic Force Generation

Abstract: The authors investigated the effects of low-intensity resistance training on muscle size and strength in older men and women. Thirty-five participants (age 59–76 yr) were randomly assigned to 2 groups and performed low-intensity (50% of 1-repetition maximum) knee-extension and -flexion exercises with either slow movement and tonic force generation (LST; 3-s eccentric, 3-s concentric, and 1-s isometric actions with no rest between repetitions) or normal speed (LN; 1-s concentric and 1-s eccentric actions with 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(91 citation statements)
references
References 30 publications
7
79
1
4
Order By: Relevance
“…RT at high intensity (70-85% 1-RM) typically induces a significant increase in muscle mass and function for both frail and healthy older individuals (19,24,25). However, several studies have also reported a significant increase in muscle mass with exercises at an intensity below 70% 1-RM as indicated by significant increase in muscle thickness (26) or fiber cross sectional area (27). In the current study, leg lean mass increased significantly after the 12-wk training period by an average of 2.9% (0.7-6.1% increase in leg lean mass).…”
Section: Discussionmentioning
confidence: 96%
“…RT at high intensity (70-85% 1-RM) typically induces a significant increase in muscle mass and function for both frail and healthy older individuals (19,24,25). However, several studies have also reported a significant increase in muscle mass with exercises at an intensity below 70% 1-RM as indicated by significant increase in muscle thickness (26) or fiber cross sectional area (27). In the current study, leg lean mass increased significantly after the 12-wk training period by an average of 2.9% (0.7-6.1% increase in leg lean mass).…”
Section: Discussionmentioning
confidence: 96%
“…Thus, there is a need for further studies to examine the muscular responses in the control of strength training variables, in particular, the prescription of exercise intensity from the time under tension [13,15,32]. However, there is still a lack of evidence about the TUT required to perform 8, 10 and 12-RM testing.…”
Section: Introductionmentioning
confidence: 99%
“…A caminhada com diferente impacto sobre o solo é um tipo de exercício ótimo que fortalece o aparato musculoesquelético do idoso, sendo mais efetiva do que modalidades esportivas LORD et al, 2007;STUBBS et al, 2013). Outros autores ainda sugerem a caminhada não só com impacto, mas também combinada com exercícios de força, equilíbrio e flexibilidade (WATANABE et al, 2013). Silva, Santos Filhos e Gobbi (2012) envolveram 61 idosos aleatoriamente alocados em três grupos distintos (GEx1-caminhada orientada; GEx2-caminhada sem supervisão e GC -grupo controle).…”
Section: Fortalecimento Musculoesqueléticounclassified
“…A osteoartrite é um tipo de distúrbio frequente, progressivo e lento com efeitos nefastos similares a osteoporose. Ela consiste na perda da cartilagem (articulação sinovial) e acometimento funcional do joelho, do quadril e da mão (COOTE; HOGAN; FRANKLIN, 2013); além disso, é responsável por inúmeras cirurgias (WATANABE et al, 2013). Não existem evidências de que programas de AF sejam benéficos para a prevenção da osteoartrite e nem há informação específica para a sua restrição.…”
Section: Fortalecimento Musculoesqueléticounclassified
See 1 more Smart Citation